A Specification Test for Models Estimated by GLS - Boothe, Paul; MacKinnon, James G. (The Review of Economics and Statistics, 1986)
We develop a new specification test which can easily be applied to regression models that have been estimated by generalized least squares. The test is a variant of the F-test. It is derived for the general case, and also, in more detail, for the commonly encountered case of models with AR(1) errors. Two empirical examples are presented, one of them involving a well-known model of exchange rate determination.